Treatment Outcomes in Advanced Biliary Tract Cancers: Single Institution Retrospective Analysis - Pathi, Nikhil; Rajappa, Senthil J.; Ayyagari, Santa; Mohan, M V. T. Krishna; Kumar, Pavan; Pinninti, Rakesh; Ladda, Pallavi; Kandem, Sanath; Tewani, Rohan; Shah, Kinjal; Bajaj, Kripa; Krishnaiah, Sree Rama; Gandrala, Divya (Indian Journal of Medical and Paediatric Oncology, 2024)
Purpose Biliary tract cancers (BTCs), particularly gallbladder cancers (GBCs), are prevalent in India. Yet there are limited data on treatment outcomes. To bridge this gap, we performed an analysis of advanced BTC treatment outcomes at our institute, seeking to offer insights into real-world scenario.Materials and Methods This is a retrospective study comprising advanced BTC patients treated at our institute from January 2015 to March 2023. We assessed demographics, treatment approaches, progression-free survival (PFS), overall survival (OS), and associated toxicities.Results Of the 411 patients analyzed, the majority were GBC (67.3%, n = 277), while the rest were cholangiocarcinoma (CCA) (32.6%, n = 134). The median age of study population was 56 years. Palliative chemotherapy was administered in 85% (n = 349) of all patients. Gemcitabine–cisplatin doublet was the most commonly used chemotherapy regimen (80.2%, n = 280). Platinum doublets yielded higher response rates compared with single-agent/nonplatinum chemotherapy (60 vs. 30%, n = 133). The median PFS was 4 months. The median OS was 8 months with platinum doublets and 5 months with single-agent/nonplatinum chemotherapy (hazard ratio [HR]: 0.60, 95% confidence interval: [CI] 0.43–0.84, p = 0.0001). OS was no different based on the type of platinum agent used. Patients receiving multiple lines of treatment lived longer compared with those who received single line only (14 vs. 6 months, respectively, HR: 0.36, 95% CI: 0.28–0.45, p < 0.0001). Significant prognostic factors for OS were treatment with chemotherapy, platinum doublets, platinum exposure in first line, and treatment beyond first line. Grade 3 or 4 adverse effects seen were anemia (13.9%, n = 36), vomiting (4.2%, n = 11), diarrhea (3.4%, n = 9), thrombocytopenia (3.4%, n = 9), and febrile neutropenia (3.1%, n = 8).Conclusion This analysis confirms that chemotherapy is beneficial for advanced BTC. Platinum-based doublets are more effective than single agents. There is no significant difference between cisplatin and oxaliplatin. Patients who received multiple lines of treatment had better OS.
Keywords: advanced biliary tract cancers; first-line chemotherapy; outcomes